COMPUTER VISION SYSTEMS APPLICATION TO ASSESS THE IMPACT OF MOBILE MACHINES ON THE GROUND SURFACE DURING WOOD HARVESTING - Lusta , Yurii; Shchupak, Andriy (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
The prospects for implementing computer vision systems for monitoring the environmental consequences of forestry machinery operation are analyzed. The feasibility of transitioning from traditional field measurements to innovative remote sensing technologies, in particular mobile laser scanning and photogrammetry, is substantiated. The possibilities of using deep learning algorithms of U-Net and YOLO models for automating the identification of technological tracks and their characteristics in real time are described. The main technical limitations and potential of integrating visual systems with CAN bus data for creating an ecological risk map are identified.